PERSONAL BRANDING MAKE UP ARTIST MELALUI INSTAGRAM(Studi Kasus Personal Branding Make Up Artist Melalui Instagram) - Mia Tania (CV. ADIBA AISHA AMIRA, 2023)
Personal branding is used by make up artists to achieve their success carrier. The strategy uses the characteristics of personal branding and impression management as an effort made interestingly by way of a variety of creative content that shows their expertise all about make up and personalities. Instagram was chosen as the best media to display photos, videos and other features that support each of their content posts. Research on personal branding make up artist via instagram uses a qualitative research method of the constructivism paradigm and a case study approach that describes clearly and in detail and obtains in-depth data from the case under research. Data collection techniques used in this research were interviews, observation, documentation and literature. while the data analysis technique is data reduction, data presentation and conclusion, and data validity using triangulation. The results of this research are the personal branding strategy used by make up artists, there are elements of personal branding and impression management that exist in their creative content, in fact those elements are only partially used, the results have not been maximized. An interesting finding from researchers is that the use of instagram only functions as a digital portfolio, unconsciously that the most effective marketing technique is word of mouth